The high notes : a novel [compact disc, unabridged] - Steel, Danielle (Recorded Books, 2022)
Iris Cooper has been singing ever since she can remember. After years of hardship, exploitation, and abuse, her big chance finally comes to do what she loves. But Iris still has to fight every step of the way.